How Long Will It Take to Lift One Billion People Out of Poverty? - Ravallion, Martin (World Bank, Washington, DC, 2013)
Alternative scenarios are considered for reducing by one billion the number of people living below $1.25 a day. The low-case, "pessimistic," path to that goal would see the developing world outside China returning to its slower pace of growth and poverty reduction of the 1980s and 1990s, though with China maintaining its progress. This path would take another 50 years or more to lift one billion people out of poverty. The more optimistic path would maintain the (impressive) progress against poverty since 2000, which would instead reach the target by around 2025-30. This scenario is consistent with both linear projections of the time series data and non-linear simulations of inequality-neutral growth for the developing world as a whole.